METODE DISCOVERY LEARNING UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK DALAM PEMBELAJARAN OLAHRAGA - NOVIANINGSIH, BETHI (Jurnal Riset Daerah, 2022)
This study discusses physical education learning, this is because physical education is considered a difficult lesson, because the material being studied contains physical activity and movement and a combination with the ability of the problems that occur lie in the learning method and learning media. The discovery learning model is a good learning model to use and has a high effectiveness value in the success of various learnings including physical education learning. The purpose of this study was to increase the activeness of students with the discovery learning model of physical education learning in the 2013 curriculum. This study used a Classroom Action Research design. The research subjects were 27 students of class XI IPS 2 consisting of 3 men and 24 women. The research activity was carried out in 3 cycles, which previously started with a pre-cycle. In the implementation of cycle 1, the students' activity got a classical percentage of 56.85% and was classified as less active. This is due to the lack of mental readiness of students to learn with the discovery learning method. Analysis of the results of observations in the first cycle of 56.85% and classified as less active. The application of the discovery learning method in cycle 2 was better than cycle 1, seen from the educators and students, the result of the classical activeness percentage was 69.25% quite active. The learning activity of students in cycle 2 has increased compared to cycle 1 with the percentage of active learning of 56.85%. So the learning activity of students increased by 12.40% from 56.85% to 69.25%. In cycle 3 using the discovery learning method is good.